Spark plasma sintering of highly magnetic Fe3O4 and CoFe2O4 ceramics from hollow spheres synthesized by thermal plasma spraying - Shanenkov I. I. Ivan Igorevich; Tsimmerman (Cimmerman) A. I. Aleksandr Igorevich; Nassyrbayev (Nasyrbaev) A. Artur; Nikitin D. S. Dmitry Sergeevich; Ivashutenko A. S. Alexander Sergeevich; Zhumabaev I. Iskander; Shanenkova Yu. L. Yuliya Leonidovna; Sivkov A. A. Aleksandr Anatolyevich; Li Junzhi; Han Wei (2025, 2025)
Title screen